Effect of humic acid on some growth characteristics of Rocket Eruca sativa Mill. (Journal of Hama University, 2025)
A field experiment was carried out in the village of Jiboul, in the countryside of the city of Jableh, during the 2023/2024 agricultural season, to study the effect of humic acid on some growth characteristics of Rocket a “local” variety. It included three treatments (0, 4, and 8 kg/ha of potassium humate), which were added In two batches, the first batch two weeks after planting, and the second one month after planting. The experiment was designed in a completely randomized block design with three replications, and the averages were compared using the Least Significant Difference (L.S.D.) test at a 5% significance level.The results showed a significant effect of humic acid on all the studied traits. The rate of 8 kg/ha of ponassium humate was significantly superior to the rest of the studied rates in all the studied traits except for the dry weight trait, which was superior to the control only, and the rate of 8 kg/ha achieved the highest average in the traits: Plant height (60.10 cm), leaf length (15.25 cm), leaf width (5.25 cm), root length (13.50 cm), fresh weight (56.00 g), and dry weight (6.35 g).
Keywords: Rocket, humic acid, potassium humate, growth.